2013
DOI: 10.1097/rlu.0b013e318279fd5a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quantitative Criteria for Glioma Grading With Static and Dynamic 18F-FDopa PET/CT

Abstract: Static and dynamic imaging without blood sampling can discriminate between LG and HG for both newly diagnosed and recurrent gliomas. In dynamic imaging, excellent discrimination was obtained by considering the transport rate constant k1 of tumors. In static imaging, the best discrimination based on SUV was obtained for SUV(mean) calculated from a 5-minute acquisition started at 38 minutes after injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 10 publications
3
40
1
Order By: Relevance
“…Similarly, in the study published by Schiepers et al, the tumor FDOPA uptake peak activity was reached around 20 min p.i [5]. In two more recent studies, the TACs of tumor FDOPA uptake peaked earlier at 8-10 min p.i [9,13]. However, the EANM/EANO/RANO practice guidelines/SNMMI procedure standards for imaging of gliomas using PET recently recommended a 10-20 min image acquisition performed 10-30 min p.i [8].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Similarly, in the study published by Schiepers et al, the tumor FDOPA uptake peak activity was reached around 20 min p.i [5]. In two more recent studies, the TACs of tumor FDOPA uptake peaked earlier at 8-10 min p.i [9,13]. However, the EANM/EANO/RANO practice guidelines/SNMMI procedure standards for imaging of gliomas using PET recently recommended a 10-20 min image acquisition performed 10-30 min p.i [8].…”
Section: Discussionsupporting
confidence: 57%
“…For routine clinical interpretation, semiquantitative measures of tumor activity uptake values are calculated [8]. However, kinetic parameters obtained through dynamic acquisition might provide further details about tumor characterization [5,9]. For instance, information regarding tumor aggressiveness from FDOPA PET/CT could have utility in guiding biopsy [10], and potentially improve patient management with dose-escalation using intensity-modulated radiotherapy in patients with glioma [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In e we report the PET/MRI fusion imaging and in f the T2-weighted MRI FDOPA in PBT according to their grade of malignancy. While the wash out of [ 18 F] FDOPA in normal tissues is relatively slow (with the concentration of [ 18 F] FDOPA over time being quietly constant), high-grade tumors are usually characterized by a rapid wash out as compared to low grades [21,22]. Another possible explanation of the differences in SUVr values could be sought in the different timings in the acquisition of PET scans in our study (15 min) as compared to that of Karunanithi (15-30 min) [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, reports are conflicting. Studies by Fueger et al [88], Pafundi et al [89] and Nioche et al [90] reported that FDOPA PET could discriminate between high and low-grade primary glioma. However, as part of their study, Chen et al found no significant difference in FDOPA uptake between the two classes.…”
Section: -[ 18 F]fluoro-dihydroxy-l-phenylalanine (Fdopa)mentioning
confidence: 99%